EVALUATION OF BIOACTIVE CONSTITUENTS AND IN-VIVO ANTI-INFLAMATORY ACTIVITY OF HYDROALCOHOLIC LEAVES EXTRACT OF GREWIA HIRSUTA - Jaiswal, Mr. Mahendra; Tyagi, C.K.; Budholiya, Prabhakar (Journal of Biomedical and Pharmaceutical Research, 2021)
Plants represent the main source of molecules for the development of new drugs, which intensifies the interest of transnational industries in searching for substances obtained from plant sources, especially since the vast majority of species have not yet been studied chemically or biologically, particularly concerning anti-inflammatory action. Anti-inflammatory drugs can interfere in the pathophysiological process of inflammation, to minimize tissue damage and provide greater comfort to the patient. Therefore, it is important to note that due to the existence of a large number of species available for research, the successful development of new naturally occurring anti-inflammatory drugs depends mainly on a multidisciplinary effort to find new molecules. Although many review articles have been published in this regard, the majority presented the subject from a limited regional perspective. Thus, the current article presents highlights from the published literature on plants as sources of anti-inflammatory agents. A search for effective medication with lesser or no side effects is the need of the hour. Hence the current study is focused at evaluating the anti-inflamatory  potential of Grewia hirsuta. The leaves of G. hirsuta were subjected to solvent extraction with ethanol. The best screened extract was further evaluated for it phytochemical profile by qualitative and quantitative phytochemical analysis. The results of the study suggest that Grewia hirsuta possesses significant anti-inflamatory potential. With further mechanistic studies it can be proved as a better source of natural anti-inflamatory agents.